دراسة أثر التّضخّم في مستوى معيشة الأسرة السّوريّة خلال الفترة 2000-2010 - الرفاعي, عبد الهادي; محمد, سالي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
نظرا لأهمية التضخم في أي نظام اقتصادي في العالم ، فإن دراسة مسبباته وآثاره يعتبر من الأولويات لما للتضخم من تأثير مباشر على مؤشرات عديدة في الاقتصاد المحلي مما ينعكس بشكل مباشر في مستوى معيشة الأسرة، لذلك تناول البحث دراسة أثر ظاهرة التضخم في مستويات المعيشة من خلال بيان أثر التضخم على كل من الدخل والذي يعبر عن مستوى معيشة الأسرة، وسعر صرف الليرة السورية كونه إحدى أهم أدوات التأثير في النمو والاستقرار الاقتصادي سواء على الصعيد الداخلي أم على صعيد العلاقات الاقتصادية الدولية التي تؤثر بشكل مباشر في مستوى المعيشة وذلك خلال الفترة الممتدة من عام 2000 الى عام 2010 ، وكان من اهم النتائج التي توصل اليها البحث من خلال الدراسة الوصفية والتحليلية وجود أثر متبادل بين معدلات التضخم والدخل وسعر صرف الليرة السورية .According to the importance of the inflation in any economical system in the world, therefore studying its causes and effects is considered a priority due to its direct influence on various indicators in the local economy. This reflects directly on the families living status.Therefore, the research has studied the influence of inflation in the levels of living through showing the effect of inflation on the income, which reflects the family's living level, and the exchange rate for the syrian pound as the most important tool effecting the economical growth and stability, wether domestically or internationally, and this directly effects the living levels between 2000 and 2010.The most important results of the analytical and decriptional study was the occurance of a reciprocal effect between inflation rates, income and the syrian exchange rate.